2015
DOI: 10.1021/acs.energyfuels.5b01094
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Biological Stability of a Terpene-Based Advanced Biofuel and Its Relationship to the Corrosion of Carbon Steel

Abstract: Energy-dense terpene biofuels have recently been recognized as renewable alternatives for high-density petroleum-derived fuels. While the physicochemical properties of terpene dimer fuel (TDF) have been well-documented, the propensity of these mixtures to undergo biodegradation and exacerbate the corrosion of the fuel infrastructure remains unknown. Coastal seawater/sediment incubations were amended with TDF or a blend of petroleum-derived hydrocarbons and incubated under strict anaerobic conditions. In some i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…36 Presumably, D. alkanexedens strain ALDC T27 was primarily responsible for oxidizing these hydrocarbons. However, the prospect of indigenous microorganisms contributing to the overall metabolism of these substrates, via the same or by different mechanisms, 11 cannot be ruled out. Since the exogenously added n-alkanes in the fuel were certainly in excess, quantification of microbial metabolism by substrate utilization against the large background signal was not possible.…”
Section: ■ Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…36 Presumably, D. alkanexedens strain ALDC T27 was primarily responsible for oxidizing these hydrocarbons. However, the prospect of indigenous microorganisms contributing to the overall metabolism of these substrates, via the same or by different mechanisms, 11 cannot be ruled out. Since the exogenously added n-alkanes in the fuel were certainly in excess, quantification of microbial metabolism by substrate utilization against the large background signal was not possible.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Coastal seawaters that are typically used to fill carbon-steel ballast tanks were used as both medium and inoculum sources. Given the potential differences in microbial community composition and water chemistry, three geographically distinct seawaters from Key West (KW), Florida; the Gulf of Mexico (GoM), Alabama; and San Diego Bay (SDB), California, were collected as previously described and shipped to the University of Oklahoma . Sediment from SDB was also used in some experiments since it is routinely introduced into ship ballast systems and serves as a source of anaerobic microorganisms. , The seawater and sediment samples were stored at 4 °C until use.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the high-density petroleum resulting fuels, Liang et al, 2015 reported renewable substitutes as energy-dense terpene biofuels. Coastal sediment/seawater developments incubated underneath simple anaerobic circumstances and were revised with TDF or a mixture of consequential petroleum hydrocarbons [37].…”
Section: Green Inhibitorsmentioning
confidence: 99%